TATA KELOLA SISTEM INFORMASI PEMERINTAHAN DAERAH (SIPD): (Studi pada Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah (BP4D) Kabupaten Belu) - Ronald Abanit Asa (Jurnal Administrasi Publik, 2022)
The Regional Government Information System or SIPD is an innovative government strategic step to create a good governance for administration and management systems as well as public services. SIPD is used by BP4D of Belu Regency to prepare development planning and budgeting documents more efficiently, effectively and effectively. This study uses qualitative methode to explain the SIPD govenance from the user's point of view. This writing aims to explain the governance of SIPD by looking at the indicators, namely strategic alignment, value distribution, resource management, risk management and performance measurement.The results of the research showed that SIPD governance was not running well where the strategic alignment aspect between planning and budgeting aspects had not been integrated optimally. In the management of human resources, the research found insufficient technical training leading to some of the personnel did not fully understand in operating the system. The performance measurement in terms of the printed document format does not satisfy the users. As the solution, it is necessary to develope the maturity of SIPD through the real needs of users and doing sustainable tech